Pelvic Organ Prolapse Quantifi cation Accuracy for Elongasio Cervix Diagnose in Pelvic Organ Prolapse Patients: Akurasi Pelvic Organ Prolapse Quantifi cation untuk Diagnosis Elongasio Serviks pada Pasien Prolaps Organ Panggul - Tyas Priyatini; Finish Fernando; Lucky S. Widyakusuma; shirley T. Anggraeni; Kukuh W. Kustarto (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: To know sensitivity, specificity and accuracy of Pelvic Organ Prolapse Quantification (POP-Q) to measure cervical length for cervical elongation diagnose in Pelvic Organ Prolapse (POP) patients with gold standard was the anatomical cervical length from hysterectomy result. Methods: Diagnosis research, cross-sectional, consecutive sampling. POP-Q was taken before the operation and the anatomical cervical length was from hysterectomy result Results: Sixty six subject, 1.5% 2nd stage POP, 45.5% 3rd stage POP, and 53.0 % 4th stage POP. Mean (± sd) age and body mass index consecutively59.88 years (± 9.347) and 24.41 (± 3.67) kg/m2. Median (min-max) cervical length POP-Q and anatomy consecutively 4 cm (1-12) and 5 cm (3-10). Sensitivity, Specificity dan Accuracy POP-Q consecutively 79%, 58% dan 68% Conclusion: POP-Q has good specificity (79%) but with less sensitivity (58%) with accuracy 68% to diagnose cervical elongation in POP Keywords: accuracy, cervical elongation, cervical length, pelvic organ prolapse, pelvic organ prolapse quantification (POP-Q), sensitivity, specificity. Abstrak Tujuan: Untuk mengetahui nilai sensitivitas, spesifisitas dan akurasi Pelvic Organ Prolapse Quantification (POP-Q) untuk menilai panjang serviks sebagai diagnosis elongasio serviks pada pasien POP dengan baku emas pengukuran anatomi serviks dari hasil histerektomi. Metode: Uji diagnosis, potong lintang, consecutive sampling. Data diambil dari pemeriksaan POP-Q dan pengukuran anatomi serviks dari hasil histerektomi. Hasil : Enam puluh enam subjek, 1,5% POP derajat 2, 45,5% POP derajat 3 dan 53,0 % POP derajat 4. Rerata(± sb)usia dan Indeks Massa Tubuh (IMT) berturut – turut 59,88 tahun (± 9,347) dan 24,41 (± 3,67) kg/m2. Median (min-maks) panjang serviks POP-Q dan anatomi berturut – turut 4 cm (1-12) dan 5 cm (3-10). Sensitivitas, spesifisitas, dan akurasi POP-Q berturut – turut 79%, 58% dan 68% Kesimpulan : Pemeriksaan POP-Q memiliki spesifitas yang baik (79%) tetapi dengan sensitivitas yang kurang baik (58%) dan akurasi 68% untuk diagnosis elongasio serviks pada prolaps organ panggul. Kata kunci: akurasi, elongasio serviks, panjang serviks, prolaps organ panggul, pelvic organ prolapse quantification (POP-Q), sensitivitas, spesifisitas